Estudo dos pares de Cooper fotônicos e sua relação com os formalismos da teoria BCS da supercondutividade e da teoria da superfluidez - Julie Priscilla Souza dos Santos (2022)
The correlated Stokes-anti-Stokes (SaS) Raman scattering occurs with the creation of a Stokes (S) and anti-Stokes (aS) photon pair where the phonon created by the S process is annihilated by the aS process. This process is said to be mediated by a virtual vibrational mode where the photon-photon interaction can be considered similar to the electron-electron interaction in the BSC supercondutivity theory, also called Cooper Pairs. In this work, we report a study and propose a theorical modeling for SaS correlated photon pairs, using a common approach from condensed matter physics. The proposal starts from conventional eletronic superdutivity, BCS theory, in which the operations are performed with commutation relations for fermions. Then, the superfluidity theory is presented as a base theory for the study of the analogy between fotonics pairs SaS and eletronics Cooper pais from BCS theory. In sequence, a theoretical review about the fotonic pairs SaS and a review about Raman process are made, followed by some experimental results who corroborate the study of fotonic pairs SaS in analogy with eletronic Cooper pairs. Finally, the construction based on photonic Cooper pairs is proposed, with operations that respect the anticommutation relations usual for bosons, where the Bugoliubov approximation can be considered, defining some properties of the system.